Sex-related preferences for real and doll’s faces versus real and toy objects in young infants and adults - Escudero, Paola (2013)
Findings of previous studies demonstrate sex-related preferences for toys in 6-month-old infants: Boys prefer non-social or mechanical toys such as cars, while girls prefer social toys such as dolls. Here, we explored the innate versus learned nature of this sex-related preferences using multiple pictures of doll and real faces (of men and women) as well as pictures of toy and real objects (cars and stoves). Forty-eight 4- and 5-month-old infants (24 girls) and 48 young adults (24 women) saw six trials of all relevant pairs of faces and objects, with each trial containing a different exemplar of a stimulus type. The infant results showed no sex-related preferences; infants preferred faces of men and women, regardless of whether they were real or doll’s faces. Similarly, adults did not show sex-related preferences for social versus non-social stimuli, but, unlike infants, they preferred faces of the opposite sex over objects. These results challenge claims of an innate basis for sex-related preferences for toy and real stimuli preferences (Connellan et al., 2000) and suggest that sex-related preferences result from maturational and social development, which continues into adulthood.